Congklak Game to Develop Cognitive and Motor Skills in Early Childhood - Abdul Rahman (Yayasan Zia Salsabila, 2023)
This research aims to describe the congklak game in developing cognitive and motor skills in young children. This research uses a qualitative approach with a literature study method. From the research results, the aim of the congklak game is that teachers can develop cognitive and motor skills in children. Thus, the game of congklak not only includes traditional games but also games that can develop cognitive and motor skills in children. If the teacher wants to develop children's cognitive and motor skills, the teacher can use congklak games as a method in developing children's cognitive and motor skills.